A thermal network model for monitoring IGBT chip solder degradation based on feedback PI control. (November 2022) - Zhang, Xiaotong; Mu, Wei; Lv, Chunlin; Shi, Miao; Yu, Xiaoling; Wu, Kangning; Li, Jianying
Abstract: Under long-term thermal cycles, the solder layers in IGBT modules degrade inevitably, which affects their heat dissipation performance and eventually leads to the failure of IGBT modules. In order to monitor the degradation degree of the IGBT chip solder layers according to the junction temperature, a thermal network model for monitoring the IGBT chip solder degradation based on feedback PI control is proposed. Firstly, the finite element simulation model of the IGBT module is established and the degradation degrees of the chip solder layers are defined in the simulation model. Then the thermal network model is extracted according to the finite element simulation model and the thermal impedance functions are fitted from the different power loss and chip solder degradation degrees. Meanwhile, a control loop with PI controller is established to regulate the thermal impedances. Finally, the accuracy of the proposed thermal network based on feedback PI control for chip solder degradation monitoring and junction temperature calculation is verified under different chip solder degradation degrees. Highlights: The specific degradation of chip solder is defined in IGBT module. A thermal network based on feedback PI control is proposed. The proposed thermal network can monitor the chip solder degradation degree.